Uneven transmission of traditional knowledge and skills in a changing wildmeat system: Yangambi, Democratic Republic of Congo - Shephard, Samuel; Muhindo, Jonas; Nyumu, Jonas; Mbangale, Emmanuela; Nziavake, Sagesse; Cerutti, Paolo; van Vliet, Nathalie (Frontiers in Conservation Science, 2023)
Indigenous communities typically hold diverse traditional ecological knowledge (TEK) of their socialecological system. Much of this knowledge is embodied as skills related to subsistence practices within a specific landscape and is associated with community values and norms. Ways of knowing often reflect the different activities traditionally undertaken by men and women. The incursion of external forces, including urbanisation, the cash economy and migration tends to diminish transmission of traditional embodied skills. Knowledge can be lost as culturally significant environments degrade or species become extirpated. Lack of opportunity to develop traditional knowledge and skills can diminish feelings of place and identity, and thus capacity for local environmental stewardship.The Yangambi region, Democratic Republic of Congo is a hunting territory of the Turumbu ethnic group. We used questionnaires to explore how levels of wildmeat knowledge and skill may have changed over time among the Turumbu. The responses showed lower levels of self-reported skill among women who started to participate in the last 10-15 years. This pattern partly reflects the period of 'apprenticeship' but may also suggest diminished learning opportunity in recent years.Skills in cooking, smoking, and selling wildmeat persist at a higher level than skills in curing disease and gathering wild produce. There was a much more marked pattern for men, with diminishing levels of wildmeat skill reported for around 35-40 years, and even earlier for knowledge of traditional medicine and wildmeat taboos. Questions about mentoring suggested that women have maintained knowledge pathways between mother and daughter, while men showed a shift towards increased learning from uncles.Gender differences in sharing and learning TEK may be linked to the type of skills that remain valuable in a changing social, ecological, and economic context. Men traditionally undertake the capture elements of hunting, while women deal with wildmeat processing, marketing, and cooking. The Yangambi wildmeat system has evolved from subsistence to a strongly market-driven economy during the lifetime of our study participants. This shift may partly explain why market-based skills such as food smoking and selling have endured longer than hunter's nature-based knowledge.